Disparitas Penuntutan Pada Perkara Tindak Pidana Penganiayaan dalam Sistem Pemidanaan di Indonesia - Saragih, Benny Leonard; Ediwarman, Ediwarman; Zul, Muaz (ARBITER: Jurnal Ilmiah Magister Hukum, 2019)
Difference in punishment or sentencing disparity is basically a natural thing because it can be said almost no case that is really the same. Disparity becomes a problem when the range of the sentence imposed differences between similar cases so large, giving rise to injustice and can give rise to suspicions in the community. Disparities in the Criminal (disparity of sentencing) is not the same as the application of criminal offenses against the same (same offense) or the criminal acts that are dangerous to be compared (offenses of comparable seriousness) without clear justification. Based on Law No. 16 of 2004 which replaced Law No. 5 of 1991 About the Prosecutor of the Republic of Indonesia is an institution in the field of prosecution of the main authority of the public prosecutor act prosecution about what is meant by the prosecution as well as the reference to the provisions of Article 1 point 7 and Article 137 Law No. 8 of 1981 on the Law of Criminal Procedure Code (Criminal Code). Research Methods in writing this thesis carried out by the method of normative law, namely analyzing and searching for answers to the problems raised by the substantive law / legal norms contained in the rules of law, the Supreme Court Regulation (PERMA), the Supreme Court Circular, and etc. Factors that cause the disparity criminal offense namely Legislation Provisions factors, internal factors and external factors.